Penerapan ASP.NET Dalam Membangun System Inventory Dengan Menggunakan Metode Prototype - Daffa Athallah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The development of business within the region of technological progress changing very rapidly, this contains a great impact and effect on the enterprise. These multiple impacts are a challenge for a service and goods company. If the corporate isn't competitive, the corporate goes bankrupt. one in every of the impacts and effects is that the application of computerization to each system within the company. Inventory is a very central part of a company's assets. The system was developed using ASP.NET and using MySQL database. The prototype method is employed because the event method. While the recording machine testing method is predicated on data entry on each page within the inventory system. the target is to implement inventory system to simplify and save time in entering inventory reports. This web system will make it easier for workers.